From the Tree to the Labyrinth - UMBERTO ECO (Harvard University Press, 2014)
At the second congress of the International Association for Semiotic Studies (Vienna, July 1979) I presented a number of â€œProposals for a History of Semiotics.â€ I recommended that we intensify historical studies on the various theories of the sign and of semiosis over the centuries, fi rst of all because I considered it a necessary contribution to the history of philosophy as a whole, and secondly because I was convinced that to do semiotics today one needed to know how it was done yesterday, however much it might have been disguised as something else. And what better place to begin than from that â€œCoup dâ€™oeil sur le dÃ©veloppement de la sÃ©miotiqueâ€ with which Roman Jakobson had opened the fi rst international congress of the association fi ve years earlier? I suggested three lines of research. Th e fi rst had narrower ambitions, since it was confi ned to those authors who had spoken explicitly about the relation of signifi cation, starting with the Cratylus and with Aristotle, down through Augustine and eventually to Peirceâ€” but without neglecting the authors of treatises on rhetoric like Emanuele Tesauro or the theorists of universal and artifi cial languages like Wilkins or Beck. My second line of research involved a close rereading of the whole history of philosophy with a view to fi nding implicit semiotic theories even where they had apparently not been explicitly developed, and the chief example I gave was that of Kant. Finally, my third suggestion was intended to cover all those forms of literature in which symbolic and hermeneutical strategies of any kind were deployed or developed (among them, for instance, the works of the Pseudo- Areopagite). I cited as examples manuals of divination (texts like Guglielmo Dorandoâ€™s Rationale divinorum offi ciorum), the medieval bestiaries, the various discussions of poetics, down to the marginal notes of writers and artists who had refl ected in one way or another on the pro cesses of communication.